Ecohealth trainer manual - Basuno, E.; Borin, B.; Crocetti, E.M.; Fèvre, S.; Horwitz, P.; Nguyen Thanh Huong; Fang, J.; Maskhao, P.; McCullagh, S.; Morrison, K.; Hung Nguyen-Viet; Stephen, C.; et al. (Veterinarians without Borders, 2013)
This training manual, and the Field Building Leadership Initiative (FBLI) of which it is one component, is part of a global initiative to build capacity in ecosystem approaches to health. Although several books and journals provide materials for learners about Ecohealth, the FBLI Ecohealth Trainer Manual is intended primarily for lecturers, teachers, and trainers. The focus here is on how to teach Ecohealth, providing teachers and trainers with a starting point from which to explore, improvise, adapt, and develop diverse educational Ecohealth learning experiences for and with their participants.